Making a Spectacle of Yourself: The Effect of Glasses and Sunglasses on Face Perception. (June 2019) - Graham, Daisy L.; Ritchie, Kay L.
We investigated the effect of wearing glasses and sunglasses on the perception of social traits from faces and on face matching. Participants rated images of people wearing no glasses, glasses and sunglasses on three social traits (trustworthiness, competence and attractiveness). Wearing sunglasses reduced ratings of trustworthiness. Participants also performed a matching task (telling whether two images show the same person or not) with pairs of images both wearing no glasses, glasses or sunglasses, and all combinations of eyewear. Incongruent eyewear conditions (e.g., one image wearing glasses and the other wearing sunglasses, etc.) reduced performance. Further analysis comparing performance on congruent and incongruent eyewear trials showed that our effects were driven by match trial performance, where differences in eyewear decreased accuracy. For same-eyewear-condition pairs, performance was poorer for pairs of images both wearing sunglasses than no glasses. Our results extend and update previous research on the effect of eyewear on face perception.